Empirical analysis of demand for roof tiles: Example of Tondach company - Jasmin Hoso (UTMS Journal of Economics, 2016)
In a very dynamic and volatile business environment, multinational companies view the intra-company exchange as a factor of developing the enterprise's capacities and total revenue growth. The paper is aimed at performing econometric evidence of the total revenues of 'Tondach' company, based on the collected economic indicators of 'Tondach' company development in nine countries. For each individual country, variables on total revenue, total company's investment in the country, the number of employees and the value of intra-company exchange were used. Besides these variables, the model will use two additional ones: population and rating for each individual country. It was established that the intra-company exchange has a positive and significant effect on the total revenue of companies in the Tondach Group in the observed countries and the observed period of time. With respect to rating, as the second independent variable of special interest, we observe a positive and strong effect on total revenue. This result also proves our claim that countries in the region, with a higher risk factor, which are not members of the integration, have a lower rating, which in turn has a direct impact on lower revenues.
Keywords: F23; F21; F14; 330; multinational company; intra-company exchange; integration; intra-firm trade; foreign direct investment